Functional feed ingredients modulate the immune response of RTgutGC cells to LPS-induced inflammation - Fosse, Malene Malchus; Méndez, Laura Rivera; Rodríguez-Ramos, Tania; Dixon, Brian; Sundh, Henrik; Olsen, Rolf Erik (Frontiers in Immunology, 2025)
Functional feed ingredients can enhance the fish gut integrity and immune resilience during challenging situations in the aquaculture industry. This study used the RTgutGC cell line – derived from rainbow trout intestinal epithelium, to evaluate the immunomodulatory and barrier effects of selected ingredients. These included β-glucan from Saccharomyces cerevisiae (BG40 and BG60), laminarin extracted from Laminaria hyperborea (Lam60 and Lam90), and bioactive peptides with antioxidative and immunomodulatory potential; carnosine (Carn100 and Carn120) and salmon hydrolysate (FPH300 and FPH600). Cells were exposed for 24 hours at two concentrations (maintaining 100 % and 80 % viability), and effects on transepithelial resistance (TEER), permeability (Papp) and gene expression (qPCR) were assessed before and after a 6-hour lipopolysaccharide (LPS) challenge. High-dose laminarin and both salmon hydrolysate concentrations elevated mRNA encoding for pro-inflammatory cytokines (il6, il8, il1b and tnfa; p < 0.05). All ingredients except carnosine significantly reduced TEER (p < 0.05) often with downregulation of barrier genes. Low-dose carnosine and laminarin reduced Papp of Lucifer yellow, indicating less barrier disruption. LPS induced inflammation, barrier dysfunction and reduced proliferation. These effects were modulated by high-dose β-glucan and both laminarin concentrations, which significantly reduced il6 expression (p < 0.05). High-dose salmon hydrolysate also tended to reduce il6 (p = 0.05) and increased pcna expression (p < 0.001), suggesting tissue recovery. Low-dose laminarin and both carnosine concentrations upregulated cldn3 post-challenge (p < 0.05). These findings support the RTgutGC model as a valuable screening tool and provides new insights into the biological activity and immunomodulatory effects of various functional feed ingredients.